Analisis Karakteristik Morfometri Sub DAS Karang Mumus Menggunakan Aplikasi HEC-HMS - Astutik Ariningsih; Feri Fadlin; Dwi Agung Pramono; Shabri Indra Suryalfihra (Journal of Geomatics Engineering, Technology, and Science, 2025)
The Karang Mumus sub-watershed is located in an urban area, making it vulnerable to development pressures and land use changes. Morphometric analysis of the Karang Mumus sub-watershed plays a crucial role in understanding the physical characteristics of the area and their relationship to water resource management and flood disaster mitigation in Samarinda City and its surrounding regions. This study aims to examine the morphometric characteristics of the Karang Mumus sub-watershed through the processing of DEMNAS data using the HEC-HMS 4.10 application. The results show that the Karang Mumus sub-watershed is divided into 15 sub-sub-watersheds, with a total area of 318.98 km². The sub-sub-watershed with the longest river channel is sub-sub-watershed 1, with a channel length of 18.57 km, while the shortest is sub-sub-watershed 12, with a channel length of 1.05 km. The average slope/gradient of the main river channel in the Karang Mumus sub-watershed is 0.15 m/m. The drainage density index of the Karang Mumus sub-watershed falls into the medium classification (0.25–10 km/km²). In terms of shape, the Karang Mumus sub-watershed is classified as elongated, with a Roundness Coefficient (RC) of 0.03 km.